Detrimental Impact of Na Upon Rb Postdeposition Treatments of Cu(In, Ga)Se2 Absorber Layers. Issue 9 (14th July 2021) - de Wild, Jessica; Birant, Gizem; Thiruvallur Eachambadi, Raghavendran; Kohl, Thierry; Buldu, Dilara G.; Brammertz, Guy; Manca, Jean V.; Meuris, Marc; Poortmans, Jef; Vermang, Bart
Abstract : Passivation of the Cu(In, Ga)Se2 (CIGS)/Mo back contact using AlO x is studied to reduce the recombination at this interface. Herein, RbF postdeposition treatment (RbF‐PDT), a well‐established method to improve absorber and front interface properties is used on back‐passivated solar cells. It is found that this combination deteriorates the performance due to formation of an injection barrier at the front and reduced acceptor concentration. Photoluminescence yield and decay times show no indication of increased defect recombination, as both are improved. With time‐of‐flight secondary ion mass spectroscopy, in‐depth and lateral alkali profiles are measured. It is shown that the Na concentration is higher at the AlO x /Mo back contact and that Rb accumulates at the CdS/CIGS interface. It is hypothesized that Na at the back is released during the RbF‐PDT and inhibits Rb diffusion into the CIGS layer. Rb remains at the front and acceptor concentration is reduced. Modeling of dark and light current–voltage characteristics shows that the injection barrier and low doping are responsible for the reduced V oc and fill factor (FF). It is suggested that the commonly observed FF losses upon heavier alkali PDT can be eliminated by adapting the initial Na amount. Abstract : RbF postdeposition treatment is performed on AlO x back‐passivated solar cells. While these treatments improve the performance separately, the combination deteriorates the performance. It is found that Na at the AlO x /Mo back inhibits Rb diffusion into the absorber layer. This leads to a detrimental redistribution of the alkali causing an injection barrier and reduction of the acceptor concentration.